Prediction of small‐for‐gestational‐age neonates: screening by placental growth factor and soluble fms‐like tyrosine kinase‐1 at 35–37 weeks. (18th June 2015) - Fadigas, C.; Peeva, G.; Mendez, O.; Poon, L. C.; Nicolaides, K. H.
ABSTRACT Objective To investigate the potential value of maternal serum placental growth factor (PlGF) and soluble fms‐like tyrosine kinase‐1 (sFlt‐1) at 35–37 weeks' gestation in the prediction of delivery of small‐for‐gestational‐age (SGA) neonates, in the absence of pre‐eclampsia (PE). Methods This was a screening study in singleton pregnancies at 35–37 weeks, including 158 that delivered SGA neonates with birth weight < 5th percentile and 3701 cases unaffected by SGA, PE or gestational hypertension. Multivariable logistic regression analysis was used to determine if measuring serum levels of PlGF and sFlt‐1 improved the prediction of delivery of SGA neonates provided by screening with maternal characteristics and medical history (maternal factors), and estimated fetal weight (EFW) from fetal head circumference, abdominal circumference and femur length. Results Compared to the normal group, the median PlGF multiples of the median (MoM) was significantly lower and the median sFlt‐1 MoM was significantly higher in the SGA group. Combined screening by maternal factors and EFW at 35–37 weeks predicted, at 10% false‐positive rate (FPR), 90%, 92% and 94% of SGA neonates with birth weight < 10th, < 5th and < 3rd percentiles, respectively, delivering < 2 weeks following assessment; the respective values for SGA delivering ≥ 37 weeks were 66%, 73% and 80%. When PlGF and sFlt‐1 were added to a model that combines maternal factors and EFW, sFlt‐1 did not remain as a significant independent predictor of SGA < 5th. Combined screening by maternal factors, EFW and serum PlGF, predicted, at a 10% FPR, 88%, 96% and 94% of SGA neonates with birth weight < 10th, < 5th and < 3rd percentiles, respectively, delivering < 2 weeks following assessment and the respective values for SGA delivering ≥ 37 weeks were 64%, 75% and 80%. Conclusion sFlt‐1 does not provide significant independent prediction of SGA, in the absence of PE, in addition to combined testing by maternal factors and fetal biometry at 35–37 weeks; whilst the addition of PlGF alone marginally improves the performance of screening. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.